The effect of the quality of stadium flooring on the level of skill performance Injuring the fencers' lower limbs (Texas Journal of Multidisciplinary Studies, 2024)
The research aims to investigate the effect of the quality of stadium flooring on both the level of skill performance of fencers and injury to the lower extremity of fencers . The descriptive survey method was used as it suits the nature of this research and its objectives. The research population and sample numbered (35) fencing players (for epee, epee, or sword). The basic sample for the research was chosen intentionally from fencers who were injured in the lower extremity on the same type of court